2013
DOI: 10.4236/ajps.2013.47a1007
|View full text |Cite
|
Sign up to set email alerts
|

Viability and Action of CPL Lectin on <i>in Vitro</i> Germinability of Pollen Grains of <i>Malpighia emarginata</i> DC.—(Malpighiaceae)

Abstract: This study aimed to observe the viability of the pollen grains of Malpighia emarginata DC. (West Indian cherry) and the action of a lectin in their germination. Lectins are proteins that specifically interact with carbohydrates, but don't modify them and bind with high affinity and specificity, promoting a transfer of information that is clearly central to many cellular processes in living beings. For the viability test was used aniline blue in lactophenol. The in vitro germination test used was the hanging dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…In another study, the expression of an agglutinin gene in the stems and both male and female flowers of Castanea crenata trees was interpreted as a possible regulatory step controlling the interaction between male gametophyte and pistil sporophytic tissues (Nakamura et al, 2004). This evidence concurs with other reports describing the localization of lectins in floral tissues of several other plant species where they have been proposed to play roles in diverse reproduction-related processes such as pollen and pollen tube development, pollen germination, male fertility and self and nonself pollen-stigma interactions (Clarke and Knox, 1978;Wu et al, 1993;Santos Sousa et al, 2013;Vakhania et al, 2014;Peng et al, 2020). Additionally, the localization of AhN4L-1 in the abscission zone of the stigma and stamens suggested the possibility that this protein could also be involved in the abscission of floral organs in plants, which is a process that requires the generation of weakened abscission zones produced, among other factors, by the activity of cell wall remodeling hemicellulose-and pectindegrading proteins (González-Carranza et al, 2002.…”
Section: Discussionsupporting
confidence: 87%
“…In another study, the expression of an agglutinin gene in the stems and both male and female flowers of Castanea crenata trees was interpreted as a possible regulatory step controlling the interaction between male gametophyte and pistil sporophytic tissues (Nakamura et al, 2004). This evidence concurs with other reports describing the localization of lectins in floral tissues of several other plant species where they have been proposed to play roles in diverse reproduction-related processes such as pollen and pollen tube development, pollen germination, male fertility and self and nonself pollen-stigma interactions (Clarke and Knox, 1978;Wu et al, 1993;Santos Sousa et al, 2013;Vakhania et al, 2014;Peng et al, 2020). Additionally, the localization of AhN4L-1 in the abscission zone of the stigma and stamens suggested the possibility that this protein could also be involved in the abscission of floral organs in plants, which is a process that requires the generation of weakened abscission zones produced, among other factors, by the activity of cell wall remodeling hemicellulose-and pectindegrading proteins (González-Carranza et al, 2002.…”
Section: Discussionsupporting
confidence: 87%
“…This pollen was sown on the same day of the collection and was kept for 24 h at 25 °C. The estimated number of germinated pollen grains was determined using an optical microscope, considering as germinated those grains of which pollen tube was longer than twice its diameter (Sousa et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, for plants of the genera Petunia and Eruca, the involvement of pistil and stamen lectins in the regulation of self-incompatibility and the pollination process was assumed (Shivanna et al, 1985). In addition, it was found that lectins of some species are directly involved in the growth of the pollen tube in vitro (Matveeva et al, 2007;Sousa et al, 2013).…”
Section: Lectin Activity In Different Flower Morphs Pistils and Stame...mentioning
confidence: 99%
“…Lectins have been reported to act as signaling molecules in the pollen/stigma recognition process in self-incompatibility (Sousa et al, 2013;Sharma et al, 1985). Given the high levels of lectins with different specificities present in L. perenne stamens and pistils, we tested the effect of the isolated lectins on self-incompatibility in the different flower morphs of L. perenne.…”
Section: The Effect Of Lectin Treatment On Self-incompatibility In He...mentioning
confidence: 99%
See 1 more Smart Citation